Kualitas Pelayanan Dalam Pembuatan Administrasi Kependudukan Di Dinas Kependudukan Dan Pencatatan Sipil Kota Surakarta Tahun 2024 - Syamsidar, Syamsidar; Tri Haryanto, Aris; Winduro, Wirid (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research aims to describe the quality of service in creating population administration. The type of research used in this research is a qualitative descriptive method. The data collection techniques used were (1) interviews (2) observation (3) documentation. The data analysis techniques used are data collection, data presentation and conclusion drawing. The results of this research show that the quality of service in making Population Administration based on the 5 indicators proposed by Parasuraman, et al, namely the tangible dimension is adequate and has satisfied the applicant. Meanwhile, there are still shortcomings in the ease of accessing services, namely that there are still many people who do not know that services are online. Based on the Responsiveness dimension, it is quite good in responding to applicants, but there are some applicants who do not respond well due to miscommunication between employees and applicants, and also online facilities and infrastructure are not responded well because errors often occur and applicants have to contact the Population Service for action. continued and took quite a long time. Judging from the reliability dimension, assurance dimension and empathy dimension, it has been implemented well and the public is satisfied with the services provided by the Surakarta City Population and Civil Registration Service. Researchers provide recommendations for improving or updating online service procedures, improving the quality of the online registration application/web so that there are no frequent errors when operated by the public and promoting the official Surakarta City Dispendukcapil website to the public. Keywords: Population administration, Service Quality